Legal Protection for Customers against Unauthorized Transactions on Stolen Contactless Debit Cards: Bank Liability and Loss Handling Mechanisms - Suwandi; Anggriawan, Teddy Prima (Program Studi Magister Hukum Universitas Malikussaleh, 2026)
The evolution of non-cash payment, specifically debit cards with contactless features, offers a quick transaction speed through a mechanism that doesn’t require a Personal Identification Number (PIN) for certain nominals. However, this convenience is directly proportional to the risk of misuse or unauthorized transactions if the card is stolen, considering that the system does not actively verify the cardholder's identity. This study aims to analyze the forms of legal protection for customers as well as the mechanisms for dispute resolution and recovery of losses for unauthorized transactions on stolen contactless debit cards. The research method used is normative legal research based on literature studies with a statutory approach and a conceptual approach. The primary legal materials used include the Indonesian Civil Code, the Law on the Development and Strengthening of the Financial Sector, and the Financial Services Authority Regulation (POJK) Number 22 of 2023 (POJK PKM SJK). The results show that legal protection for customers includes preventive protection through the bank's obligation for information transparency and regulatory that is required, as well as repressive protection through a loss compensation claim mechanism. Banks as payment system providers have the primary responsibility to ensure the security of the products offered. If an unauthorized transaction occurs due to the characteristics of the contactless product design, the bank cannot fully release its responsibility. However, customers also have an obligation to safeguard the card and immediately report its loss, where customer negligence can be a limiting factor for loss compensation based on the principle of proportionality. Dispute resolution mechanisms are carried out in stages through internal bank complaints, non-litigation settlement through the Alternative Dispute Resolution Institution for the Financial Services Sector (LAPS SJK), and litigation as a last resort (ultimum remedium). The enactment of POJK PKM SJK emphasizes that financial services sector dispute resolution is now focused on LAPS SJK, replacing the role of the Consumer Dispute Resolution Agency (BPSK) in this realm